1985
DOI: 10.1159/000115823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GM<sub>1</sub> Ganglioside in Cerebrovascular Diseases: A Double-Blind Trial in 40 Cases

Abstract: A randomized, double-blind trial on the effects of GM1 ganglioside in cerebrovascular diseases was done on 40 patients; the treatment (40 mg/day i.m. injection) began after the acute phase and lasted 6 weeks. 18 cases took the drug and 16 the placebo. The evaluation of the cases was made by graduating the severity of the clinical signs, and some neurophysiological and morphological parameters, i.e., EEGs, flash-evoked potentials and computer tomography scans. We found that the drug, in comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…These observations led Willinger ( 198 I ) to suggest that GMl may be necessary for the normal maturation of neurons in the cerebellum. Since that time, it has been observed that the addition of gangliosides to neuroblastoma cells maintained in vitro results in the induction of neuritogenesis (Roisen et al, 198 I;Byrne et al, 1983;Facci et al, 1984;Carine and Schengrund, 1984;Nakajima et al, 1986) and gangliosides have also been shown to enhance nerve regeneration in vivo (Battistin et al, 1985;Horowitz, 1986;Huaman et al, 1986;Haferkamp, 1987).…”
mentioning
confidence: 99%
“…These observations led Willinger ( 198 I ) to suggest that GMl may be necessary for the normal maturation of neurons in the cerebellum. Since that time, it has been observed that the addition of gangliosides to neuroblastoma cells maintained in vitro results in the induction of neuritogenesis (Roisen et al, 198 I;Byrne et al, 1983;Facci et al, 1984;Carine and Schengrund, 1984;Nakajima et al, 1986) and gangliosides have also been shown to enhance nerve regeneration in vivo (Battistin et al, 1985;Horowitz, 1986;Huaman et al, 1986;Haferkamp, 1987).…”
mentioning
confidence: 99%
“…Two trials in ischemic and hemorrhagic stroke have demonstrated beneficial effects of GM 1 at a dose of 40 mg/day im for a period of 6 weeks, starting as late as 10-15 days after the onset of the stroke. There were statistically significant differences in neurological scores when the ganglioside group was compared with placebo-treated controls (60,61).…”
Section: Sygen 6 In Cns Disordersmentioning
confidence: 92%
“…In vitro and in vivo treatment with GM 1 or GM 1 -L (siagoside) attenuates EAA-related neuronal death in a dose-dependent manner even when administered systemically (for review, see Leon et al 1990). First clinical trials in stroke patients were initiated in the early 1980s (Bassi et al 1984;Battistin et al 1985). However, two large trials were finished in 1994 without convincing evidence of efficiacy for this therapeutic approach (Alter et al 1994;Lenzi et al 1994) Neurotrophic factors and other growth factors Based on the neurotrophic factor hypothesis (Barde 1989), lack of trophic support was suggested to cause secondary neuronal death after neuronal trauma.…”
Section: Gangliosidesmentioning
confidence: 99%